Metamodel for integration of Internet of Things, Social Networks, the Cloud and Industry 4.0 - Cueva Lovelle, Juan Manuel; Montenegro, Carlos Enrique; Rainer, J Javier; González-Crespo, Rubén (Journal of Ambient Intelligence and Humanized Computing, 2017)
Internet of Things (IoT) is changing the world. Software for manufacturing industry is perceived as the new industrial revolution. It is creating new opportunities for both the economies and the society. Deployment of Internet of Things for development of Industry 4.0 changes processes and manufacturing systems while it also changes players in a wide variety of types and shapes. In that sort of systems, information is related to manufacturing status, trends in energy consumption by machinery, movement of materials, customer orders, supply data and all data related to smart devices deployed in the processes. This paper analyzes Internet of Things (IoT), its use into manufacturing industry, its foundation principles, available elements and technologies for the man-things-software communication already developed in this area. And it proves how important its deployment is. Describes a proposal of architecture of the Internet of things applied to the industry, a metamodel of integration (Internet of Things, Social Networks, Cloud and Industry 4.0) for generation of applications for the Industry 4.0, and the manufacturing monitoring prototype implemented with the Raspberry Pi microcomputer, a cloud storage server and a mobile device for controlling an online production process.
Keywords: JCR; Scopus